Análisis del riesgo de control en procesos administrativos financieros de la empresa Obcemsa S.A. - Torres Herrera, Petita Rocio (2021)
Companies for their progress have prepared multiple systems or tools that will be implemented in their administrative process according to your company; This process may have its own adaptations depending on the size or type of company, service or product it provides; This establishes a certain complexity that requires a specific control of the risks that this system may entail immersed in its adaptation. The administrators in charge of executing this risk control seek to support each and every one of their human and economic resources in the development of their work activities, they must consider the notorious value that will be added if it is carried out effectively and efficiently or otherwise the devaluation that will affect its image as an entity, its service or product and its projection in the market. This research work will allow knowing and analyzing the importance of compliance with the administrative process specifically in the financial area of an entity; inasmuch as it will really assess the effectiveness of the management of the referred entity. Allowing you to consider your true competition. to the administrators of the company and its future projection.